Biomarkers in low cardiac output syndrome after open cardiac surgery in children - Reby Kusumajaya; Najib Advani; Piprim B. Yanuarso; Zulham Effendy (Indonesian Pediatric Society, 2021)
Background Corrective cardiac surgery is the standard management for complex congenital heart disease. Cardiopulmonary bypass surgery and post-surgical intensive care may lead to low cardiac output syndrome (LCOS), as a major complication after open heart surgery. To diagnose early LCOS, lactate level, pCO2 gap, and mixed venous oxygen saturation (SvO2) are parameters reported to have correlations with decreased cardiac output, morbidity, and post-cardiac surgery mortality. Objective To determine the usefulness of lactate level, pCO2 gap (arterial-vein), and SvO2 for early detection of LCOS in children post-open heart surgery. Methods This prospective cohort study was done from August to October 2017 in the ICU of the Integrated Cardiac Center, Dr. Cipto Mangunkusumo Hospital, Jakarta. Subjects were pediatric patients who underwent cardiac surgery. After surgery, patients underwent monitoring in the ICU for clinical signs of LCOS and examinations for lactate levels, pCO2 gap, and SvO2 at 15 minutes, 4 hours and 8 hours. Results Thirty-three open heart surgery patients were the subjects. Lactate level at 4 hours and 8 hours post-operative were significantly higher in the LCOS group compared to non-LCOS group. For the pCO2 gap, only the 4-hour post-operative results were significantly higher in LCOS group compared to non-LCOS groups. In addition, only SvO2 at 4 hours after surgery was significantly lower in LCOS group compared to non-LCOS group. Conclusion Elevated lactate, high pCO2 gap, as well as decreased SvO2 at 4 hours post-operatively are the most reliable markers of LCOS after pediatric open heart surgery.